2022
DOI: 10.3389/fneur.2022.865920
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on MRI for White Matter Hyperintensity of Presumed Vascular Origin and Cognitive Impairment

Abstract: White matter hyperintensity of presumed vascular origin (WMH) is a common medical imaging manifestation in the brains of middle-aged and elderly individuals. WMH can lead to cognitive decline and an increased risk of cognitive impairment and dementia. However, the pathogenesis of cognitive impairment in patients with WMH remains unclear. WMH increases the risk of cognitive impairment, the nature and severity of which depend on lesion volume and location and the patient's cognitive reserve. Abnormal changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…On the clinical level, we found that a higher burden of WMLs was associated with lower cognitive performance, even after controlling for health-related factors. These findings are consistent with previous research [21], highlighting that cognitive changes can be observed at a prodromal stage of disease. Stronger effects were generally found for the immediate recall of words.…”
Section: Discussionsupporting
confidence: 93%
“…On the clinical level, we found that a higher burden of WMLs was associated with lower cognitive performance, even after controlling for health-related factors. These findings are consistent with previous research [21], highlighting that cognitive changes can be observed at a prodromal stage of disease. Stronger effects were generally found for the immediate recall of words.…”
Section: Discussionsupporting
confidence: 93%
“…These changes can include a reduction in white matter volume, disrupted white matter tracts, and an increase in white matter lesions. Such alterations can contribute to cognitive decline and dementia [ 64 , 65 ], indicating that cardiovascular disease have the potential to affect the integrity of the brain’s white matter and, consequently, its cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have only examined functional or anatomical changes in isolation. In recent years, with the rapid development of multimodal MRI technology, researchers have carried out a large number of neuroimaging studies on the structural and functional damage to the brain caused by CSVD (Liu et al, 2019 ; Meng et al, 2022 ). Studies have shown that changes in brain function are often accompanied by changes in the structure of the corresponding brain regions.…”
Section: Introductionmentioning
confidence: 99%